2011
DOI: 10.3109/09553002.2011.568572
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol inhibits hypoxia-inducible factor-1 pathway

Abstract: Our data suggest that honokiol can exert its anticancer activity as a HIF-1α inhibitor by reducing HIF-1α protein level and suppressing the hypoxia-related signaling pathway. The animal experiment indicates that honokiol improves the therapeutic efficacy of radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Hypoxic tumors tend to be more aggressive, more likely to metastasize, more resistant to conventional therapies, and are associated with a poor prognosis [4]–[6]. The gene encoding HIF1 (hypoxia-inducible factor-1), which is composed of the HIF1α and HIF1β subunits, is perhaps the most studied gene that plays an essential role in the response to hypoxia [7]. HIF1α is stable under hypoxic conditions, with its expression rapidly decreasing under normoxic conditions, whereas HIF1β is constitutively expressed under both conditions [8].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxic tumors tend to be more aggressive, more likely to metastasize, more resistant to conventional therapies, and are associated with a poor prognosis [4]–[6]. The gene encoding HIF1 (hypoxia-inducible factor-1), which is composed of the HIF1α and HIF1β subunits, is perhaps the most studied gene that plays an essential role in the response to hypoxia [7]. HIF1α is stable under hypoxic conditions, with its expression rapidly decreasing under normoxic conditions, whereas HIF1β is constitutively expressed under both conditions [8].…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been reported that Honokiol obtained from Magnolia grandifloris and used for thousands of years in traditional Asian medicine modulates HIF at different levels. Honokiol regulates the HIF-1a protein accumulation as well as its transcriptional activity in subcutaneous murine colon carcinoma [98].…”
Section: Modulation Of Hif Post-translationmentioning
confidence: 99%
“…Adaptation of tumor cells to the hypoxic conditions depends on the hypoxia-inducible factor 1 (HIF-1), a transcriptional activator of cell survival, proliferation, angiogenesis, invasion and metastasis genes [6,7]. Recently, it has been demonstrated that a specific set of microRNAs (miRNAs) molecules are upregulated by hypoxia [8].…”
Section: Introductionmentioning
confidence: 99%